Reports of his death have been greatly exaggerated - Goodhand, James (Mira, 2025)
"A lifetime ago, Ray 'Spike' Thorns was a well-regarded caretaker on a boarding school's grounds. These days, he lives the life of a recluse in a house rammed with hoarded junk, alone and disconnected from family or anyone he might have at one time considered a friend. When his next-door neighbor drops dead on Spike's doorstep, a case of mistaken identity ensues: according to the police, the hospital, the doctors--everyone--Spike is dead. Spike wants to correct the mistake, really he does, but when confronted with those who knew him best, he hesitates, forced to face whatever impression he₂s left on the world. It's a discovery that brings him up close to ghosts from his past, and to the only woman he ever loved. Could it be that in coming face-to-face with his own demise, Spike is able to really live again? And will he be able to put things straight before the inevitable happens--his own funeral? This is the best kind of feel-good fiction: it's deeply affecting but full of clever mishaps and enough laughs along the way. It takes the message from Dead Poets Society and mixes it with the tragedy of It's a Wonderful Life and tops it off with an ultimately lovable guy like in A Man Called Ove. The result is a heartbreakingly beautiful look at life and what we would all do if given a second chance."--